Analysis of clinical and microbiological data on Acinetobacter baumannii strains assist the preauthorization of antibiotics at the patient level for an effective antibiotic stewardship program. Issue 5 (September 2017) - Swe Swe-Han, Khine; Mlisana, Koleka P.; Pillay, Manormoney
Abstract: Drug resistant Acinetobacter baumannii ( A. baumannii ) poses serious treatment challenges and is on the rise worldwide. The Infectious Diseases Society of America/Society for Healthcare Epidemiology of America recommends preauthorization of antibiotics to ensure successful antibiotic stewardship programs (ASWPs). This study estimates and analyzes the microbiological and clinical characteristics of A. baumanii strains with differentiating criteria for sepsis versus colonization, in order to support preauthorization and assist ASWPs at the patient level. A retrospective observational study was performed from 2008 to 2014. The clinical and microbiological characteristics of A. baumannii strains were correlated to assess pathogenic status and antibiotic resistance patterns. A flow chart was produced to differentiate between sepsis and colonization amongst patient groups. A. baumannii was cultured in 2656 cases, with a prevalence of 0.9–2.4% during 7 years study periods. There was a statistically significant difference between the sepsis and colonization groups (P = 0.02). Sepsis accounted for 37–51% of A. baumanii isolates and colonisation for 49–63% (P = < 0.01). Multidrug resistant (MDR), extensive drug resistant (XDR) and pandrug resistant (PDR) A. baumannii was detected in 53–60%, 1–19% and 1% of cultures in the sepsis group, and 75%, 8–23% and 1% in the colonized group. There was a high percentage of polymicrobial infection in the sepsis group and pure growth was not always significant for sepsis. Cases of MDR and XDR A. baumannii increased over the seven-year study, while PDR strains emerged. For a successful ASWP, both clinical and microbiological information should be interpreted when establishing preauthorization/decision to treat.